Handwörterbuch rechtsextremer Kampfbegriffe - Gießelmann, Bente; Kerst, Benjamin; Richterich, Robin; Suermann, Lenard; Virchow, Fabian (Wochenschau Verlag, 2019)
http://www.wochenschau-verlag.de/handwoerterbuch-rechtsextremer-kampfbegriffe-2850.html